Polar bear skin rug on the floor of the NWT Legislative Assembly Chamber - Campbell, Sandy (2015)
This polar bear skin rug lies on the floor of the NWT Legislative Assembly Chamber. There is a story that the tour guides tell about it. A man asked the Legislative Assembly to help him because the bear was terrorizing the settlement. The Assembly did not help, so he killed the bear and brought the hide to the Assembly.